Capturing the Aerobiome: Application of Polyurethane Foam Disk Passive Samplers for Bioaerosol Monitoring - Kalisa, Egide; Saini, Amandeep; Lee, Kevin; Mastin, Jacob; Schuster, Jasmin K; Harner, Tom (American Chemical Society (ACS), 2024)
Bioaerosols are ubiquitous and play a significant role in global climate and human health due to inhalation exposure. Passive air sampling of bioaerosols, as a complementary method to active sampling using pumps, is increasingly valued due to its simplicity, electricity-free operations, and cost-effectiveness in providing time-integrated samples over weeks/months. In this study, polyurethane foam disk passive air samplers (PUF-PAS), passive dry deposition air samplers (PAS-DDs), and active high-volume (Hi-Vol) air samplers were deployed in Toronto and the Athabasca oil sands region (OSR) in the first stages of a proof-of-concept exercise for bioaerosols. Airborne bacterial and fungal communities were characterized using MiSeq DNA sequencing. All sampler types were shown to successfully collect bioaerosols. The dominant bacterial and fungal phyla observed by all samplers were qualitatively similar. Species richness and community structure of the airborne bacterial and fungal communities varied with sites and seasons. Principal coordination analysis indicated that bacterial and fungal communities differed between Toronto and OSR. Further work is required to calibrate and characterize the uptake of PUF-PAS and PAS-DD for bioaerosols to derive quantitative information on their abundance to better assess sources and potential exposure risks.
Keywords: 3107 Microbiology; 31 Biological Sciences; 41 Environmental Sciences; 4105 Pollution and Contamination